Study on the effects of Mogroside V in inhibiting NLRP3-mediated granulosa cell pyroptosis and insulin resistance to improve PCOS - Wenqin Yang; Yujie Ma; Yafei Wu; Xiaocan Lei; Jing Zhang; Meixiang Li (Journal of Ovarian Research)
Abstract Objective Polycystic Ovary Syndrome (PCOS) is a prevalent endocrinopathy in reproductive-aged women, contributing to 75% of infertility cases due to ovulatory dysfunction. The condition poses significant health and psychological challenges, making the study of its pathogenesis and treatment a research priority. This study investigates the effects of Mogroside V (MV) on PCOS, focusing on its anti-inflammatory and anti-insulin resistance properties. Methods Forty-five female Sprague–Dawley rats were divided into three groups: control, PCOS model, and MV treatment. The PCOS model was induced using a high-fat diet and letrozole. The MV treatment group was subsequently administered MV after the establishment of the PCOS model. The study monitored body mass, assessed estrous cycle changes, and measured serum hormone levels. Transcriptome sequencing and bioinformatics were used to identify differentially expressed genes related to inflammation and insulin resistance. Expression of pyroptosis and insulin resistance markers was analyzed using qRT-PCR, Western blot, and IHC. Additionally, an in vitro model assessed MV's impact on inflammation and insulin resistance. Results The PCOS group exhibited elevated serum testosterone (T), luteinizing hormone (LH), insulin, and fasting glucose levels, along with increased insulin resistance (HOMA-IR) and decreased estradiol (E2), which were reversed by MV treatment. Transcriptome analysis identified significant gene expression changes between groups, particularly in pathways related to NLRP3 inflammation and insulin metabolism. MV treatment normalized the expression of ovarian pyroptosis factors (NLRP3, Caspase-1, GSDMD) and inflammatory cytokines (IL-1β, IL-18). In cellular models, MV increased E2 levels, reduced LDH release, and decreased the expression of insulin resistance and pyroptosis markers. Correlation analysis showed pyroptosis factors were positively correlated with HOMA-IR and IGF1, and negatively with IGF1R and E2 levels. Conclusion MV improves PCOS by reducing pyroptosis and insulin resistance, enhancing insulin sensitivity, and promoting estrogen synthesis, thereby restoring granulosa cell function and follicular development.